Hemispheric lateralization abnormalities of the white matter microstructure in patients with schizophrenia and bipolar disorder - Ho, New Fei (J Psychiatry Neurosci, 2017)
BACKGROUND: Hemispheric lateralization of the brain occurs during development and underpins specialized functions. It is posited that aberrant neurodevelopment leads to abnormal brain lateralization in individuals with psychotic illnesses. Here, we sought to examine whether white matter hemispheric lateralization is abnormal in individuals with the psychotic spectrum disorders of schizophrenia and bipolar disorder. METHODS: We examined the white matter microstructure lateralization in patients with schizophrenia, bipolar disorder with psychotic features and healthy controls by measuring the laterality indices of fractional anisotropy (FA) and mean diffusivity (MD). We also correlated the laterality indices with clinical measures. RESULTS: We included 150 patients with schizophrenia, 35 with bipolar disorder and 77 healthy controls in our analyses. Shared FA lateralization abnormalities in patients with schizophrenia and bipolar disorder were found in the cerebral peduncle and posterior limb of internal capsule, with more extensive abnormalities in patients with bipolar disorder than in those with schizophrenia. The shared MD lateralization abnormalities were more widespread, extending to the subcortical, frontal–occipital, limbic and callosal tracts, with patients with bipolar disorder showing greater abnormalities than patients with schizophrenia. While lateralization was decreased in patients with schizophrenia, the lateralization was reversed in those with bipolar disorder, underpinned by the more pronounced microstructural abnormalities in the right hemisphere. The loss of FA lateralization in patients with schizophrenia was associated with lower quality of life and psychosocial functioning. LIMITATIONS: Owing to the cross-sectional study design, we cannot confirm whether the lateralization abnormalities are neurodevelopmental or a consequence of psychosis onset or chronicity. CONCLUSION: Shared and distinct white matter lateralization abnormalities were found in patients with schizophrenia and bipolar disorder. In distinct regions of abnormalities, the lateralization was attenuated in patients with schizophrenia and reversed in those with bipolar disorder.